The philosophy of history : an introduction - Day, Mark (Mark Andrew), 1974- (London ; New York : Continuum, 2008)
Mark Day offers a lucid treatment of existing approaches to the philosophy of history, exploring subjects that include: the centrality of historical language, objections to historical truth and realism, the relationship between the philosophy of history and the philosophy of science, and much more besides.
Keywords: History -- Philosophy. -- History -- Methodology. -- History -- Study and teaching